Survival of children and adolescents with intellectual disability following gastrostomy insertion. Issue 7 (21st April 2020) - Wong, K.; Glasson, E. J.; Jacoby, P.; Srasuebkul, P.; Forbes, D.; Ravikumara, M.; Wilson, A.; Bourke, J.; Trollor, J.; Leonard, H.; Nagarajan, L.; Downs, J.
Abstract: Background: Positive health outcomes have been observed following gastrostomy insertion in children with intellectual disability, which is being increasingly used at younger ages to improve nutritional intake. This study investigated the effect of gastrostomy insertion on survival of children with severe intellectual disability. Methods: We used linked disability and health data of children and adolescents who were born in Western Australia between 1983 and 2009 to compare survival of individuals with severe intellectual disability by exposure to gastrostomy status. For those born in 2000–2009, we employed propensity score matching to adjust for confounding by indication. Effect of gastrostomy insertion on survival was compared by pertinent health and sociodemographic risk factors. Results: Compared with children born in the 1980s–1990s, probability of survival following first gastrostomy insertion for those born in 2000–2009 was higher (2 years: 94% vs. 83%). Mortality risk was higher in cases than that in their matched controls (hazard ratio 2.9, 95% confidence interval 1.1, 7.3). The relative risk of mortality (gastrostomy vs. non‐gastrostomy) may have differed by sex, birthweight and time at first gastrostomy insertion. Respiratory conditions were a common immediate or underlying cause of death among all children, particularly among those undergoing gastrostomy insertion. Conclusions: Whilst gastrostomy insertion was associated with lower survival rates than children without gastrostomy, survival improved with time, and gastrostomy afforded some protection for the more vulnerable groups, and earlier use appears beneficial to survival. Specific clinical data that may be used to prioritise the need for gastrostomy insertion may be responsible for the survival differences observed.